Islamic Economics as an Alternative Economy in Facing the Global Economic Recession - Mustafa (MultiTech Publisher, 2023)
As a scientific discipline, Islamic economics must have a complete scientific building such as a solid body of knowledge, a methodology for producing theories, theories that explain economic doctrine and reality as well as the accumulation and systematization of knowledge in Islamic economics as a body of knowledge. Islamic economics must be built on the principles of Islamic epistemology which recognizes God's revelation (al-wahy) in the form of the Qur'an and Al- Hadith as a source of knowledge, in addition to empirical facts and the accumulation of human experience (facts) and intellectual reasoning. . The Islamic economic methodology has a unified approach to the three sources of knowledge. This means that there is no dichotomy between